Pareto-Optimal Event-Based Scheme for Station and Inter-Station Control of Electric and Automated Buses - Cecilia Pasquale; Simona Sacone; Silvia Siri; Antonella Ferrara (IEEE Open Journal of Control Systems)
This paper considers electric and automated buses required to follow a given line and respect a given timetable in an inter-city road. The main goal of this work is to design a control scheme in order to optimally decide, in real time, the speed profile of the bus along the line, as well as the dwell and charging times at stops. This must be done by accounting for the traffic conditions encountered in the road and by jointly minimizing the deviations from the timetable and the lack of energy in the bus battery compared with a desired level. For the resulting multi-objective optimal control problem a Pareto front analysis is performed in the paper, also considering a real test case. Relying on the analysis outcomes, an event-based control scheme is proposed, which allows, every time a bus reaches a stop, to find the most suitable Pareto-optimal solution depending on a set of state and scenario conditions referred to the expected departure time at stops, the predicted traffic conditions in the road and the state of charge of the bus battery. The performance of the proposed control scheme is tested on a real case study, thoroughly discussed in the paper.